Extensive cranial, spinal and abdominal involvement in brucellosis: a case with review of the literature - Koç, Ali Murat; Ünsal, Yaprak; Mollamehmetoğlu, Hülya; Esen, Özgür; Bilgin, Rıfat Reha (The European Research Journal, 2019)
Brucellosis is still an endemic disease in certain parts of world. It’s clinical and radiological features are crucial for an accurate diagnosis. Although systemic disease in brucellosis shows common typical features, it’s also very important to know the uncommon features of multisystemic involvement. Herein we present a case of brucellosis with unique imaging features of extensive cranial, spinal, abdominal involvement in a middle aged woman.